Evaluating consumer behavior for consumption of milk and cheese in Gjilan region, Kosovo - Shaqiri, F.; Vasa, L.; Musliu, A.; Ymeri, P. (The Journal of Nature Studies - Annals of Agrarian Science, 2019)
The main objective of this paper was to evaluate consumers` consumption patterns of milk and cheese consumption in Gjilan Region of Kosovo by analyzing factors that influence purchasing decision for milk and cheese products. In the model of the multiple linear function quantity of milk and cheese purchased by a household within a month is a function of family size (FS), a number of children aged 14 and younger (Ch), as well as the number of employed family members (EFM). The same model was used for the total expenditure for cheese. The results of the study revealed that family size; the number of employed people and the number of children in the household had a significant impact in determining the quantity of milk and cheese consumption. The results of the research are showing that as the size of a family and number of employed family member increase by one unit, in Gjilan Region, the quantity of milk consumed goes up by 10.622 liters/month. If others variables are held constant, the quantity of milk consumed is 7.74 liters/month. The results of research are showing that exists a positive relati-onship between the quantity of cheese consumed and other three variables (family size, number of children and number of employed family members).